Photo-Targeted Nanoparticles - Dvir, Tal (2010)
We report a novel and simple proof-of-concept of a nanoparticulate system that targets any tissue selectively upon illumination. Nanoparticles were covalently functionalized with the amino acid sequence YIGSR, which adheres to the β1 integrins present on most cell surfaces. This peptide was masked with a caging group, rendering it biologically inert. Illumination with UV light released the caging group from the YIGSR, allowing binding to cells.